TAXONOMY AND PHYTOGEOGRAPHY OF GENUS CAREX L. (CYPERACEAE) IN THE KASHMIR HIMALAYA: Life Sciences-Botany - UL HAQ, EHTISHAM; DAR, G. H.; WAFAI, B. A.; KHUROO, ANZAR A. (International Journal of Life Science and Pharma Research, 2011)
The genus Carex L., one of the largest genera among angiosperms in the world, is cosmopolitan in distribution, with relatively high species richness in the temperate regions of the Northern Hemisphere. In the Kashmir Himalaya, Carex is one of the most speciose and widely distributed genera, occurring from the sub-tropical Jammu through temperate Kashmir valley to the cold-arid Ladakh region. Owing to its rich diversity and distribution, the present paper provides a taxonomic assessment and distribution status of the Carex in this Himalayan region. In total, 33 species of Carex have been recorded, which are distributed within two sub-genera: Carex and Vignea. Out of the total species recorded, the highest with 23 species are distributed in the Kashmir valley, followed by the Ladakh with 13 species and then Jammu with 8 species.